IDEALITAS PENEGAKKAN HUKUM DITINJAU DARI PERSPEKTIF TEORI TUJUAN HUKUM - Afdhali, Dino Rizka; Syahuri, Taufiqurrohman (LPPM STIH Awang Long, 2023)
In principle, laws are made to give people confidence in different interests. Through law, the ideals of legal subjects can be achieved, including legal certainty, benefit and justice. However, in the process of law enforcement, between these three legal objectives, there are often conflicts between one legal objective and another. This journal aims to determine the ideality of law enforcement from the perspective of legal objective theory. The method used in this legal research is normative juridical legal research which uses library materials as primary sources. The result of this research is that if there is tension between these basic values, then you must use the basis or principle of priority where the first priority always falls on the value of justice, then the value of usefulness or usefulness and finally legal certainty. In other words, ideally law enforcement must always prioritize and prioritize the goals of justice.